PENYULUHAN PEMBUATAN SARANA SEPTIC TANK SESUAI SNI SEBAGAI LANGKAH ODF DI DESA KARANGREJA - Uumdati, Latifatul; Dian Iva Prestiana, Novita; Maysaroh Chairunnisa, Nurlaila (An-Nizam, 2023)
The problem in Karangreja Village is the behaviour of people who still practice open defecation. The extension of private septic tank construction in Karangreja village aims to plan a private septic tank system that is able to serve users, has sufficient capacity, is easy to operate and maintain, meets applicable standards and regulations. The method of implementing community service applies the method of community education in the form of counselling. The impact of the success of this activity will be seen in the long term through improved public health, improved sanitation infrastructure, and behavioural changes towards better sanitation. In addition, a sustainable approach to maintenance and monitoring of these sanitation facilities will also be key to long-term success.